Ramet demography of Aechmea distichantha Lem. (Bromeliaceae) in two contrasting years in the understory and open areas of a South American xerophytic forest - Barberis, Ignacio Martín (2020)
The Schinopsis balansae forests of the Wet Chaco are characterized by convex areas with woody vegetation and plain areas with herbaceous vegetation. In the Wet Chaco, Aechmea distichantha is a terrestrial bromeliad that forms dense colonies in the understory and open areas of these forests. The aim of this study was to analyze the spatial and temporal variations in population dynamics of this bromeliad species. We monitored ramets growing in sun and shade conditions during two contrasting years. We analyzed the spatial and temporal variations in survival, flowering, and ramet production. Variations in survival, flowering, and ramet production were more marked between years than between habitats. During the year with wetter and milder temperature conditions, survival and ramet production were higher than during the drier year with more extreme temperatures. Survival of vegetative ramets was less variable than survival of young and reproductive ramets. In the colder year, lower winter temperatures reduced the populations in all stages, being more important in the open areas. Our results highlight the importance of low temperatures on A. distichantha demography at this xerophytic forest located at the southernmost distribution range of this bromeliad species.